Penerapan Rest API dalam Pengembangan Sistem Informasi Sayur Online Kediri berbasis Web dan Mobile (Studi Kasus: Sayuraya Kediri) - Sandi Dewo Rahmadianto; Bayu Rahayudi; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Sayuraya is a startup located in Kediri City that provides online kitchen needs. There are several problems with Sayuraya's operations. The first is that the transaction recording process is still done manually so that it is possible for human errors to occur in the recording process. The second problem is that the management system is still done manually which takes a long time and is at risk of errors. The information system to be developed uses the RAD (Rapid Application Development) method. The study begins with a needs analysis interview with the vegetable owner. Furthermore, a design will be carried out based on a needs analysis. After the design is approved, it is then implemented in the form of coding. In the implementation process, a management web was created that would be used for the vegetable company, as well as a mobile application that would be used for the vegetable customer. And use the REST API for communication between mobile applications with the server. The last stage is testing. The first test is black-box testing, in this test, 18 functional requirements have been made, and the results are all functions run correctly. The second test was carried out using the Usability method by using the System Usability Scale, in this test the questionnaire was distributed to 6 respondents, 5 were customers and 1 was the vegetable owner. from the test results get a value of 77.08.